Relationships between parental attachment, interparental conflict, anxiety in social skill performance, and self-efficacy among late adolescents in Hamadan, Iran - Parsa, Nakisa (2014)
Despite of, importance of self-efficacy in psychological and social well-being among adolescents, still there are students who suffer from low self-efficacy and consequently low academic performance. Therefore, it is important to examine factors influencing self-efficacy among adolescents. This study aims to determine the relationships between parental attachment, inter-parental conflict, anxiety to perform social skills and self-efficacy among late adolescents in Hamadan, Iran. This quantitative study used a correlational research design. Participants of this study were 374 female and male University students aged between 17-19 years old. Participants were identified by probability proportional to size sampling. Selfadministered questionnaires were used to collect data. Instruments used to measure main variables of the study are General Self-Efficacy Scale (GSE; 1995), Inventory of Peer and Parent Attachment (IPPA; 1989), The Children’s Perception of Interparental Scale (CPIC; 1992), and Scale for Interpersonal Behavior (SIB; 1984). All the instruments were highly reliable. Descriptive, bi-variate and multivariate statistics were used in data analysis. Pearson’s correlation analysis showed that mother attachment and father attachment were positively and inter-parental conflict and anxiety to perform social skills were negatively related to adolescent’s self-efficacy. The Multiple Regression Analysis showed that mother attachment, father attachment, children’s birth order, father’s occupation, mother’s education and mother’s age were significant contributors to self-efficacy. Mother attachment emerged as the strongest predictor of adolescent’s self-efficacy (Beta=.26, p<0.05). The result of study also shows that anxiety to perform social skills partially mediates the relationships between mother attachment and inter-parental conflict with self-efficacy among respondents. The results of the present study highlighted the importance of maternal and paternal factors in enhancing self-efficacy among late adolescent students in Hamadan-Iran. However, as expected, the contributions of anxiety to perform social skills as a mediator reduce the indirect relationships between parental attachment and self efficacy among respondents. The nature of anxiety to perform social skills as a mediator implied that self-efficacy of adolescents can be improved if adolescents do not experience insecurity and anxiety. Therefore, adolescents need to be equipped with appropriate skills to handle anxiety in performing social skill.